Technology Acceptance FinTech Using the Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) - Dely Indah Sari; I Made Sondra Wijaya; Adritriani Zahra; Nabila Khairunnisa (Goodwood, 2026)
Purpose: This study investigates the factors influencing FinTech acceptance using the Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) framework.Methodology: A quantitative research design was employed using an online survey of 276 Indonesian FinTech users. Data were collected from existing users and analyzed using PLS-SEM to examine the relationships among the UTAUT2 constructs, Behavioral Intention and Use Behavior.Results: Social Influence was the strongest predictor of Behavioral Intention (? = 0.489, p < 0.001), followed by Performance Expectancy, Hedonic Motivation, and Habit. Facilitating Conditions strongly influenced Use Behavior (? = 0.830, p < 0.001), while Price Value was insignificant. The UTAUT2 model explained 81.9% of Behavioral Intention and 77.9% of Use Behavior variance.Conclusions: Social Influence and Facilitating Conditions were the strongest determinants of Behavioral Intention and Use Behavior, indicating that social influence plays a more important role than perceived price value in encouraging FinTech acceptance.Limitations: The use of a cross-sectional survey design limits the ability to capture changes in user behavior and technology acceptance.Contribution: This study confirms the robustness of the UTAUT2 framework in explaining FinTech acceptance and provides practical insights for FinTech providers to enhance user-acceptance.